2021
DOI: 10.1002/hed.26607
|View full text |Cite
|
Sign up to set email alerts
|

Redefining risk of contralateral cervical nodal disease in early stage oropharyngeal cancer in the human papillomavirus era

Abstract: Background The optimal extent of surgery and/or radiation to the contralateral lymph node region is unknown in early‐stage human papillomavirus (HPV)–related oropharyngeal squamous cell carcinoma (OPSCC). Methods To investigate the pathologic incidence of and risk factors for contralateral nodal disease (CND) in cT1‐T2 HPV‐related OPSCC treated with transoral robotic surgery (TORS) and bilateral neck dissection (BND), the records of 120 patients were reviewed. Results Eleven patients displayed pathologic contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In ECOG 1308, a 15-Gy dose reduction improved both swallowing outcomes and nutritional status at 12 months posttherapy. 32 A reduction of the radiation volume to spare normal tissue and uninvolved structures should be pursued as well and has been investigated in several settings, such as omission of the contralateral neck in well lateralized tonsillar tumors, [61][62][63] use of proton beam therapy (Clini calTr ials.gov identifier NCT01893307), omission of the primary tumor bed after complete surgical resection, 64,65 and reduced elective nodal volume during definitive CRT (Clini calTr ials.gov identifiers NCT04104945 and NCT03822897) or after induction chemotherapy. 66 Modification of cisplatin-based chemotherapy is also an important goal given the otologic, renal, and neurologic adverse effects as well as the finding that it augments the late toxicity of radiation.…”
Section: What Is the Optimal Methods Of De-escalation?mentioning
confidence: 99%
“…In ECOG 1308, a 15-Gy dose reduction improved both swallowing outcomes and nutritional status at 12 months posttherapy. 32 A reduction of the radiation volume to spare normal tissue and uninvolved structures should be pursued as well and has been investigated in several settings, such as omission of the contralateral neck in well lateralized tonsillar tumors, [61][62][63] use of proton beam therapy (Clini calTr ials.gov identifier NCT01893307), omission of the primary tumor bed after complete surgical resection, 64,65 and reduced elective nodal volume during definitive CRT (Clini calTr ials.gov identifiers NCT04104945 and NCT03822897) or after induction chemotherapy. 66 Modification of cisplatin-based chemotherapy is also an important goal given the otologic, renal, and neurologic adverse effects as well as the finding that it augments the late toxicity of radiation.…”
Section: What Is the Optimal Methods Of De-escalation?mentioning
confidence: 99%
“…In contrast to the results of Last et al, Smith et al identified a 4% rate of pathologic contralateral nodal disease in 120 patients with clinical N0-1 BOT HPV+OPSCC. 9 In our study, 27 of the 29 patients with BOT tumors who underwent unilateral neck dissections had clinical N0-1 BOT HPV+OPSCC and 24 of 29 had 0-1 pathologic lymph nodes without ENE. One of these patients (4.2%) experienced a contralateral regional recurrence which was successfully salvaged with surgery.…”
mentioning
confidence: 56%
“…
We congratulate Smith et al 1 for their valuable contribution to our understanding of contralateral nodal spread in human papillomavirus-associated oropharyngeal squamous cell carcinoma.Among their entire 120 patients cohort with cT1-T2 tumors of the base of tongue or palatine tonsil, pathologic evidence of contralateral nodal disease (pCND) was found in 11 patients, or 9% of their cohort. For the subset with well-lateralized primary tumors and cN0-N1 nodal disease, pCND was found in only 2% (palatine tonsil) and 4% (base of tongue) of patients.
…”
mentioning
confidence: 94%
“…We congratulate Smith et al 1 for their valuable contribution to our understanding of contralateral nodal spread in human papillomavirus-associated oropharyngeal squamous cell carcinoma.…”
mentioning
confidence: 94%